2017
DOI: 10.1080/14756366.2016.1256883
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis and evaluation of novel cinnamic acid derivatives bearing N-benzyl pyridinium moiety as multifunctional cholinesterase inhibitors for Alzheimer’s disease

Abstract: A novel family of cinnamic acid derivatives has been developed to be multifunctional cholinesterase inhibitors against AD by fusing N-benzyl pyridinium moiety and different substituted cinnamic acids. In vitro studies showed that most compounds were endowed with a noteworthy ability to inhibit cholinesterase, self-induced Aβ (1–42) aggregation, and to chelate metal ions. Especially, compound 5l showed potent cholinesterase inhibitory activity (IC50, 12.1 nM for eeAChE, 8.6 nM for hAChE, 2.6 μM for eqBuChE and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 52 publications
0
41
0
Order By: Relevance
“…Thirdly, cinnamic acid is readily available and much cheaper compared to available AD therapeutics. Importantly, cinnamic acid derivatives have been demonstrated to function as cholinesterase inhibitors and might have therapeutic beneficial in AD ( Chen et al, 2018 ; Lan et al, 2017 ). In-vitro study by Zhang et al has shown that one of the derivatives, compound 5I, inhibits choloinesterase activity, prevents aggregation of Aβ42 and is neuroprotective against amyloid-stimulated cell toxicity ( Lan et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thirdly, cinnamic acid is readily available and much cheaper compared to available AD therapeutics. Importantly, cinnamic acid derivatives have been demonstrated to function as cholinesterase inhibitors and might have therapeutic beneficial in AD ( Chen et al, 2018 ; Lan et al, 2017 ). In-vitro study by Zhang et al has shown that one of the derivatives, compound 5I, inhibits choloinesterase activity, prevents aggregation of Aβ42 and is neuroprotective against amyloid-stimulated cell toxicity ( Lan et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies highlighted their role as an antioxidant, antiinflammatory, antidiabetic, and anticancer agents . They also possess various pharmacological properties that can work against diverse neurological disorders . A cinnamic acid 2,3‐dimethyl derivative extracted from the leaves of pycnanthus angolensis has been reported for its potential cholinesterase inhibitory activity .…”
Section: Cinnamic Acid and Its Derivativesmentioning
confidence: 99%
“…A cinnamic acid 2,3‐dimethyl derivative extracted from the leaves of pycnanthus angolensis has been reported for its potential cholinesterase inhibitory activity . Recently, a docking study suggested an interaction of N‐benzyl pyridinium moiety with the catalytic anionic site of AChE and the interaction of heterocyclic moiety with the peripheral anionic site of AChE that leads to stacking interactions . The hybrid of cinnamic acid with benzyl pyridinium is suggested to be a dual‐acting AChE .…”
Section: Cinnamic Acid and Its Derivativesmentioning
confidence: 99%
See 2 more Smart Citations